2022
DOI: 10.1007/s00267-022-01720-w
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Environmental Assessments with Cumulative Effects Scenario Modeling for Grizzly Bear Connectivity in the Bow Valley, Alberta, Canada

Abstract: Persistence of sensitive wildlife in populated regions requires conservation strategies that address gradual expansion of development footprint and human activity. The project-based environmental assessment regime for municipal development is poorly suited to provide necessary strategic perspective, given its focus on local and short-term impacts. We used the ALCES cumulative effects model to strategically assess impacts to grizzly bears (Ursus arctos) in the Bow Valley of Alberta, Canada. Landscape simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Strava Heatmap is a popular index of cumulative annual recreation intensity and is increasingly used as a proxy for human recreation (Jäger, Schirpke & Tappeiner, 2020; Corrandi et al,. 2021; Carlson et al, 2022). Previous research demonstrates that Strava Heatmap reflects the intensity of ski mountaineer activities from counting stations (Jäger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Strava Heatmap is a popular index of cumulative annual recreation intensity and is increasingly used as a proxy for human recreation (Jäger, Schirpke & Tappeiner, 2020; Corrandi et al,. 2021; Carlson et al, 2022). Previous research demonstrates that Strava Heatmap reflects the intensity of ski mountaineer activities from counting stations (Jäger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Both humans and wildlife concentrate their activities along valley bottoms and as a result these areas are disproportionately affected by human development that can lead to human-wildlife occurrences, displacement of wildlife from habitats and loss of important wildlife corridors (Alberta Government, 2018). Mirroring many mountain towns in North America, the town of Canmore has undergone growth in their permanent population, development footprint and recreation sector (Alberta Government, 2018; Carlson et al, 2022), including the increase of the creation and use of informal recreation trails (Whittington et al, 2022). While monitoring and research on recreation patterns and impacts to wildlife has been identified as a research priority in the Bow Valley (Carlson et al 2022), this work is hampered by lack of current and detailed information on human recreation activities.…”
Section: Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell-based modelling framework is flexible with respect to resolution and study area extent, such that it can be used at a range of spatial scales. However, the tool's ability to represent multiple drivers and simulate dynamics for extensive areas has seen the tool primarily used for large regions (thousands to hundreds of thousands of km 2 ) to inform land-use planning (Carlson and Stelfox, 2014), conservation planning (Carlson et al, 2019), and cumulative effects assessment (Carlson et al, 2022). While most applications, including those listed above,…”
Section: Scenario Analysis With Aomentioning
confidence: 99%